2014
DOI: 10.1210/en.2013-1624
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Steroid Modulation of Sleep and Wakefulness in Male and Female Rats Is Sexually Differentiated and Neonatally Organized by Steroid Exposure

Abstract: The paucity of clinical and preclinical studies investigating sex differences in sleep has resulted in mixed findings as to the exact nature of these differences. Although gonadal steroids are known to modulate sleep in females, less is known about males. Moreover, little evidence exists concerning the origin of these sex differences in sleep behavior. Thus, the goal of this study was to directly compare the sensitivity of sleep behavior in male and female Sprague Dawley rats to changes in the gonadal steroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 81 publications
0
59
0
1
Order By: Relevance
“…Recent findings in adult rats support this assertion and further suggest that sleep patterns in females remain sensitive to fluctuations in oestradiol while males on the other hand seem insensitive to changes in both oestradiol and testosterone [108]. Gonadectomized male and female rats exhibit no significant differences in any vigilance state.…”
Section: (A) Sex Differences In Sleep Behaviourmentioning
confidence: 78%
See 2 more Smart Citations
“…Recent findings in adult rats support this assertion and further suggest that sleep patterns in females remain sensitive to fluctuations in oestradiol while males on the other hand seem insensitive to changes in both oestradiol and testosterone [108]. Gonadectomized male and female rats exhibit no significant differences in any vigilance state.…”
Section: (A) Sex Differences In Sleep Behaviourmentioning
confidence: 78%
“…Thus, the effect of sex steroids on sleep might be chronotype dependent, such that oestradiol in rodents may work to consolidate sleep and wake behaviours to the appropriate phases. Indeed, oestradiol administered to ovariectomized rats increases the duration of total sleep in the light phase by a small but significant degree [108] (figure 3). Moreover, findings from SD studies further support that ovarian steroids and oestradiol in particular may facilitate recovery from sleep loss [121,122,125 -127].…”
Section: (A) Sex Differences In Sleep Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…R. Soc. B 371: 20150106 sleep appear to have origins in development and to be sexually differentiated by hormones in the same manner as so many other traits [95]. Inappropriate attention to sleep disorders in women has compounding effects.…”
Section: Sex Differences In Diseases and Disorders Of The Nervous Systemmentioning
confidence: 99%
“…327, 330, 332-334 Studies exploiting genetic tools to dissociate genetic and gonadal sex, along with use of classical neuroendocrine paradigms, recently showed that sex differences in sleep appear to be developmentally determined by a combination of genetic sex and gonadal hormone exposure. 335, 336 Estradiol downregulates the synthetic enzyme for PGD 2 , 337 increases Hcrt and Hcrt receptor expression levels, 338, 339 and modulates Fos expression in the VLPO and TM. 331 …”
Section: Other Neurochemicals Involved In Sleep/wake Controlmentioning
confidence: 99%